Persepsi Guru Terhadap Soal Matematika Terintegrasi Nilai-Nilai Islam Di MAN 3 Pasaman Barat - Anisa Dwi Putri; Annisa Ul Husna; Nisa Oktavia; M. Imamuddin (KOLONI, 2024)
Education in Indonesia not only aims to improve academic abilities but also to shape the character and morals of students in accordance with Islamic teachings, as the majority of the population. One relevant approach is the integration of Islamic values ​​in subjects, including mathematics, to achieve holistic educational goals. At MAN 3 West Pasaman, this integration has been implemented with the hope of enriching mathematics learning with Islamic values ​​that are relevant in everyday life. This research aims to explore teachers' perceptions of mathematics questions that are integrated with Islamic values ​​at MAN 3 West Pasaman. Qualitative research methods with a case study approach were used to understand the views, experiences and understanding of teachers in implementing this approach. The subject of this research were two mathematics teachers at MAN 3 Pasaman Barat. Data was collected through in-depth interviews, classroom observations, and document analysis. The research results show that the majority of mathematics teachers at MAN 3 West Pasaman welcome the integration of Islamic values ​​in mathematics problems. They believe that this approach not only increases students' interest and motivation but also helps build their character in accordance with Islamic teachings. However, implementation faces challenges such as lack of resources and supporting teaching materials, limited training, and limited time in the curriculum. Recommendations from this research include the need to develop comprehensive training for teachers, provide relevant resources and teaching materials, as well as flexibility in the curriculum to support the integration of Islamic values ​​without sacrificing required academic material. By understanding these perceptions and challenges, it is hoped that effective strategies can be developed to improve the quality of mathematics learning that focuses on students' cognitive, affective and spiritual aspects in accordance with Islamic values